Binge Eating Disorder (BED) in Relation to Addictive Behaviors and Personality Risk Factors - Davis, Caroline; Mackew, Laura; Levitan, Robert D.; Kaplan, Allan S.; Carter, Jacqueline C.; Kennedy, James L. (Frontiers in Psychology, 2017)
While there is good evidence that BED is linked to higher-than-expected use of a broad range of addictive behaviors, mechanisms underlying this association are not well understood. Using a mediation-analytical approach with three age- and gender-matched groups - overweight/obese adults with and without BED, and normal-weight control participants – we tested the hypothesis that adults with BED would engage in more addictive behaviors and have higher scores on a personality-risk index than the two control groups. We also anticipated that the relationship between BED and addictive behaviors would be mediated by a high-risk personality profile. The predicted mediation effect was strongly supported. Contrary to expectation BED participants did not engage in more addictive behaviors or have higher personality-risk scores than their weight-matched counterparts. However, both overweight/obese groups did have significantly higher scores than the normal-weight group. The relationships among personality risk, elevated BMI, and addictive behaviors has important clinical and implications, especially for treatments that target psycho-behavioral intervention for compulsive overeating and substance-use disorders.